Publishers and libraries in the information society : allies or rivals - Živković, Daniela (2008)
The aim of this paper is to highlight the beginning of cooperation between libraries and publishers in creating favorable conditions for the creation, distribution and reading of books in the 1960s, when rationalization and standardization started in the book sector. The author then focuses on the period from 2000 to 2008, when cooperation intensified in response to the impact of ICT on the book sector. The activities of major international organizations who were responsible for this cooperation (UNESCO, The Council of Europe, The European Commission, IFLA, IPA, The International ISBN Agency, EBLIDA, The Frankfurt Group) are described. Special attention is paid to cooperation in bibliographic control, digital rights management, and VAT, with reference to the experience of several countries including some in the Balkan region.
Projekt MZOS
ENG